Political Configuration of Law in Law Enforcement in Indonesia - Khoirunnisa; Didi Jubaidi (Yayasan Ilomata, 2023)
This article discusses the configuration of legal politics towards law enforcement and its impact on the legal system in Indonesia. The politicisation of law enforcement is one of the negative implications of legal politics that can cause injustice and imbalance in the justice system. In law enforcement, it is important for the state to ensure the independence of legal institutions, avoid politicisation of law enforcement, and increase the accountability of the justice system as well as maintain public trust in the legal system and government. This research aims to find out the impact of the development of legal politics on the law enforcement system in Indonesia and the existence of legal politics in the law enforcement system in this country. The method used in this research is a normative juridical approach. The results of the study show that Legal politics has a big role in law enforcement, often in enforcing the law the role of politics is not applied properly, where law enforcers prioritise the interests of political elites. The impact of legal politics on law enforcement has a negative impact on society and the justice system. The law should be enforced based on the principles of justice, without political interference or involvement. Law enforcement officers should not give different treatment to anyone because everyone has equal rights under the law.